2012
DOI: 10.1093/toxsci/kfs102
|View full text |Cite
|
Sign up to set email alerts
|

Irritancy and Allergic Responses Induced by Exposure to the Indoor Air Chemical 4-Oxopentanal

Abstract: Over the last two decades, there has been an increasing awareness regarding the potential impact of indoor air pollution on human health. People working in an indoor environment often experience symptoms such as eye, nose, and throat irritation. Investigations into these complaints have ascribed the effects, in part, to compounds emitted from building materials, cleaning/consumer products, and indoor chemistry. One suspect indoor air contaminant that has been identified is the dicarbonyl 4-oxopentanal (4-OPA).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
68
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(68 citation statements)
references
References 44 publications
0
68
0
Order By: Relevance
“…Oxygenated organics formed by O 3 or OH reactions can be acute or chronic irritants, and they can sorb to surfaces, oxidize further, contribute to aerosol formation, or be removed by air exchange (Aalto-Korte et al, 2005; Anderson et al, 2007, 2012; Bein and Leikauf, 2011; Jakubowski and Czerczak, 2010; Jarvis et al, 2005; Kroll and Seinfeld, 2008; Weschler, 2011). The quantification of OH indoors is challenging, but OH has been predicted or measured at ~10 −7 –10 −5 ppb (Carslaw, 2007; Sarwar et al, 2002; Weschler and Shields, 1996, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Oxygenated organics formed by O 3 or OH reactions can be acute or chronic irritants, and they can sorb to surfaces, oxidize further, contribute to aerosol formation, or be removed by air exchange (Aalto-Korte et al, 2005; Anderson et al, 2007, 2012; Bein and Leikauf, 2011; Jakubowski and Czerczak, 2010; Jarvis et al, 2005; Kroll and Seinfeld, 2008; Weschler, 2011). The quantification of OH indoors is challenging, but OH has been predicted or measured at ~10 −7 –10 −5 ppb (Carslaw, 2007; Sarwar et al, 2002; Weschler and Shields, 1996, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…While terpenes themselves are generally regarded as safe, they are highly reactive with indoor oxidants such as ozone and hydroxyl radicals [Singer et al 2006;Weschler 2000]. These reactions form highly oxidized species, including ketone and aldehyde products, many of which have shown or are suspected to cause respiratory tract effects including sensory irritation and airflow limitation [Anderson 2012;Jarvis et al 2005].…”
Section: Chemical and Biological Exposures In Farming Environmentsmentioning
confidence: 99%
“…Indoor exposures to high concentration, not typical and realistic indoor concentrations, of ozone and its initiated chemistry products, would cause adverse health effects (Anderson et al, 2012;Anderson, Khurshid, Meade, Lukomska, & Wells, 2013;Clausen, Wilkins, Wolkoff, & Nielsen, 2001;Wolkoff, Clausen, & Larsen, 2008;Wolkoff, Clausen, & Larsen, 2012;Wolkoff, Larsen, & Hammer, 2013). Studies have shown that exposures to ozone initiated chemistry products, at high end concentrations of typical indoor conditions, may cause trigeminal stimulation and possibly eye irritation (Klenø & Wolkoff, 2004;Nøjgaard, Christensen, & Wolkoff, 2005).…”
Section: Health Effectmentioning
confidence: 99%